Efficacy and safety of visually guided laser balloon versus cryoballoon ablation for paroxysmal atrial fibrillation: a systematic review and meta-analysis - Ye, Wenyi; Chen, Qian; Fan, Guangci; Zhou, Xinbin; Wang, Xiao; Mao, Wei; Li, JuanJuan (Frontiers in Cardiovascular Medicine, 2023)
Background Newly developed catheter ablation (CA) techniques, such as laser balloon ablation (LBA) and cryoballoon ablation (CBA), have been introduced in recent years and emerged as valuable alternatives to conventional radiofrequency CA strategies for paroxysmal atrial fibrillation (PAF) patients. However, evidence comparing LBA and CBA remain controversial. Thus, we conducted this meta-analysis to assess the efficacy and safety between these two techniques. Methods Scientific databases (PubMed, Embase) and relevant websites (the Cochrane Library, ClinicalTrials.gov) were systematically searched from inception to March 2023. The primary outcomes of interest were the AF recurrence and the procedure-related complications. Secondary outcomes included procedural time, fluoroscopy time, and left atrial (LA) dwell time. Results Seven clinical trials with a total of 637 patients were finally enrolled. No significant differences were found between LBA and CBA in terms of AF recurrence [16.3% vs. 22.7%, odds ratio (OR) = 0.66, 95% confidence interval (CI): 0.42–1.05, p = 0.078] or total procedural-related complications (8.4% vs. 6.4%, OR = 1.33, 95% CI: 0.71–2.51, p = 0.371). LBA had a significantly longer procedural time [weighted mean difference (WMD) = 38.03 min, 95% CI: 13.48–62.58 min, p = 0.002] and LA dwell time (WMD = 46.67 min, 95% CI: 14.63–78.72 min, p = 0.004) than CBA, but tended to have shorter fluoroscopy time. Conclusions LBA and CBA treatment have comparable efficacy and safety for PAF patients. LBA was associated with longer procedural and LA dwell times compared with CBA. Further large-scale studies are warranted to compare these two techniques with the newest generations. Systematic Review Registration: https://www.crd.york.ac.uk/prospero/display_record.php?RecordID=426513, identifier (CRD42023426513).